2009
DOI: 10.1097/brs.0b013e318194e275
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Shift on Magnetic Resonance Imaging at 24 Hours After Cervical Laminoplasty

Abstract: The posterior shift of the spinal cord at 24 hours had a tendency to shift more posteriorly than that observed at 2 weeks after cervical laminoplasty. C5 palsy may be prevented if the expansion of dura mater, which is strongly correlated with the posterior shift, can be controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 11 publications
2
43
0
Order By: Relevance
“…The most commonly cited and accepted theory for C5 nerve palsy is the 'tethering effect', whereby it is believed that an increase in posterior shift of the thecal sac after decompression of the spinal canal and restoration of anatomic lordosis puts tension on the exiting C5 nerve root and, either by ischemia or neuropraxia, causes injury. 1,[6][7][8][9] This theory is further supported by the equivalent rates of C5 palsy after both anterior and posterior cervical decompression. While the two approaches vary in technique, they both decompress the spinal canal and restore lordosis allowing for posterior shift of the thecal sac and tension on the C5 nerve root.…”
Section: Discussionsupporting
confidence: 57%
“…The most commonly cited and accepted theory for C5 nerve palsy is the 'tethering effect', whereby it is believed that an increase in posterior shift of the thecal sac after decompression of the spinal canal and restoration of anatomic lordosis puts tension on the exiting C5 nerve root and, either by ischemia or neuropraxia, causes injury. 1,[6][7][8][9] This theory is further supported by the equivalent rates of C5 palsy after both anterior and posterior cervical decompression. While the two approaches vary in technique, they both decompress the spinal canal and restore lordosis allowing for posterior shift of the thecal sac and tension on the C5 nerve root.…”
Section: Discussionsupporting
confidence: 57%
“…Another possible cause was tethering of the root after creating lordosis, which happened when the spinal cord of a patient who had posterior decompression and postoperative neurological complications shifted posteriorly by more than 5 mm during the first 24 h [22]. Takemitsu et al [20] showed that postoperative neurological deficits were detected in 50% of patients who underwent cervical spinal reconstructions using lateral mass screws and pedicle screws.…”
Section: Discussionmentioning
confidence: 99%
“…The common features were: (1) late onset after surgery, (2) unilateral weakness of the deltoid and biceps brachii muscles with or without sensory disturbance, and (3) preceding severe pain of the neck and scapular arch. Tethering of the nerve root is thought to be due to the posterior shift of the spinal cord [22]. When kyphosis of the cervical spine is corrected, the posterior shift of the spinal cord might be larger than that of cervical laminoplasty alone [25].…”
Section: Discussionmentioning
confidence: 99%
“…A relative mean improvement of 1.9 mm is then typically observed by 2 weeks. 7 Moreover, in the same study, in cases of C-5 palsy, dorsal displacement undergoes a greater positional change, drifting up to 5.5 mm whereby a decrease to about 3 mm can be seen at 2 weeks. 7 The gradual ventral rebound may explain the typical improvement that is observed.…”
Section: Discussionmentioning
confidence: 92%